Hepatic Arterial Infusion Chemotherapy versus Trans-arterial Chemoembolization in Unresectable Hepatocellular Carcinoma: : A Systematic Review and Meta-Analysis - Abuhelwa, Ziad (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.